Attitude Towards Understanding In Respecting The Existence of Differences - Rofiq, Muhammad; Laely, Amanda Luthfy; Abyan, M. Khoiru; Wardani, Putri Mutia (KOLABORASI: Journal of Multidisciplinary, 2024)
Islam as the majority religion of Indonesia has an important role and maintains harmony between religious communities. As is known in the Qur'an it is written that Islam is a religion of rahmatan lil alamin so that Islam must provide peace and tranquility everywhere, including in Indonesia. This has an impact on the process of Islamic education in Indonesia. However, the reality is that there is still often justification for the truth from each party, religious learning is still doctrinal, and the material in Islamic education is formulated and delivered with only one perspective. This study is based on the understanding of pluralism that occurs in the Islamic education system and instills an inclusive attitude in religion. This study aims to educate students to have an inclusive attitude that is able to understand the perspectives of others in terms of friendship or religion. This study uses an approach method and also an introduction to diversity and differences in terms of ethnicity, race, religion and culture in Indonesia. The results of this study are to create a future generation that can appreciate the differences and diversity that occur in Indonesia. This is based on the attitude of students who do not yet have a sense of caring and understanding of each other, whether of the same ethnicity, race, religion, or culture.